2021
DOI: 10.1080/1331677x.2021.1952640
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of COVID-19 and global financial crises: evidence from US economy

Abstract: The COVID-19 crisis has had deep adverse effects on a global level, affecting many economies and worsening their conditions which may have led to severe recession or even depression. The numbers of positive cases have risen sharply over the last few months, and the fatalities have also reached their peak. This study aims to examine the impact of the global financial crisis, and the COVID-19 pandemic on the macroeconomic variables of the US economy. It also provides an understanding in a descriptive format, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 25 publications
1
46
0
2
Order By: Relevance
“…Some people, for example, are content with their little salary and choose to live within their means rather than wait for a higher degree of financial security. On the other hand, people enjoy a high level of financial security (Taft et al, 2013 ; Sayed et al, 2020 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some people, for example, are content with their little salary and choose to live within their means rather than wait for a higher degree of financial security. On the other hand, people enjoy a high level of financial security (Taft et al, 2013 ; Sayed et al, 2020 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the Covid-19 pandemic shares similarities to other crisessuch as those in recessionary periodsit has created a crisis that is similar but also different from the crises already studied (Li et al, 2021). Much of the resulting organizational pivots required to respond to the turbulence were enacted in the short-term, while also balancing longer-term requirements (Sands and Ferraro, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Salisu et al [ 41 ] and Chudik et al [ 42 ] found that the pandemic had negative effects on the economies of many countries to varying degrees, with more profound and lasting effects on developed economies than emerging economies. In addition, some scholars have conducted studies on some countries where the pandemic was more serious, and assessed the economic shocks of the pandemic on the United States [ 43 , 44 ], Britain [ 45 ], India [ 46 , 47 ], Australia [ 48 ], Italy [ 45 ] and Canada [ 49 ] as well as its impacts on energy demand and energy consumption in the United States [ 50 ], India [ 26 ] and Canada [ 51 ].…”
Section: Literature Reviewmentioning
confidence: 99%